BENTUK KAJIAN DAKWAH DIGITAL DI INDONESIA : SISTEMATIC LITERATURE REVIEW : MUHAMMAD BURHAM - BURHAM, MUHAMMAD (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2023)
Digital da'wah is becoming a bentukd in Indonesia, both as a da'wah activity and also asa research bentukd today. Digital da'wah exists because of the penetration of digital media technology innovation in preaching, and changes in society (mad'u) in accessing da'wah. This article aims to mapping the bentukds of digital da'wah research in Indonesia, using systematic literature review method. Systematic literature review in this article involves 200 research articles on digital da'wah obtained from Google Scholar and Crossref databases in the period 2005-2021. The research instrument for systematic literature review in this article uses the Publish or Perish app to collect metadata from Google Scholar and Crossref and data visualizations using VOSviewer applications. The results of the study in the form of: 1) Mapping clusters of research themes related to digital da'wah, 2) Looking at the network of authors of digital da'wah themes and which are often a reference of research in the field of digital da'wah, and 3) Seeing the shortcomings and novelty (novelty) in digital da'wah research.